2008
DOI: 10.1002/ar.20736
|View full text |Cite
|
Sign up to set email alerts
|

Lymphangiogenesis and Its Relationship With Lymphatic Metastasis and Prognosis in Malignant Melanoma

Abstract: Regional lymph node metastasis is one of the important indicators of cutaneous malignant melanoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
57
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 35 publications
(60 citation statements)
references
References 38 publications
2
57
1
Order By: Relevance
“…Experiments with transgenic mice have shown that overexpression of VEGF-C results in lymphatic endothelial proliferation and vessel enlargement (Jeltsch et al, 1997). Likewise, the clinical significance of VEGF-C expression in relation to lymph node metastasis and patient outcome has been reported in cancers of the esophagus, stomach, and colorectum (Liu et al, 2008). Downregulation of VEGF-C or blockade of VEGFR-3 signaling inhibits lymphangiogenesis and lymph node metastasis in experimental animal cancer models (Chen et al, 2005;Lin et al, 2005;Burton et al, 2008).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Experiments with transgenic mice have shown that overexpression of VEGF-C results in lymphatic endothelial proliferation and vessel enlargement (Jeltsch et al, 1997). Likewise, the clinical significance of VEGF-C expression in relation to lymph node metastasis and patient outcome has been reported in cancers of the esophagus, stomach, and colorectum (Liu et al, 2008). Downregulation of VEGF-C or blockade of VEGFR-3 signaling inhibits lymphangiogenesis and lymph node metastasis in experimental animal cancer models (Chen et al, 2005;Lin et al, 2005;Burton et al, 2008).…”
Section: Discussionmentioning
confidence: 98%
“…Although tumor cell dissemination is mediated by a number of mechanisms, the most common pathway of initial dissemination is through the lymphatic system to the regional lymph nodes (Pepper et al, 2000). The presence of metastases in regional lymph nodes is a strong indicator of low-patient survival rate, poor patient prognosis in many types of cancer (Skobe et al, 2001;Miyahara et al, 2007;Liu et al, 2008). Despite advances in the treatment of breast cancer, morbidity and mortality from breast cancer remain unacceptably high.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…VEGF-C was immunohistochemically detected in the cytoplasm of malignant cells in 70.97% of metastatic melanoma cases and 36% of non-metastatic cases (20). Current evidence demonstrate the correlation between VEGF-C overexpression in the primary tumor and existence of lymph node metastases (36).…”
Section: Growth Factors In Malignant Melanomamentioning
confidence: 91%
“…Also, in most studies, higher LMVD values were observed in the peritumor zone than the intratumor zone, along with significant morphologialc differences. The number of peritumor lymphatic vessels is significantly larger in cases of VEGF-C and -D positive malignant melanomas than in the negative ones (10.05 vs. 6.4 and 10.07 vs. 6.3, respectively) (20). As a particularity, LMVD values may represent a discriminating aspect between metastatic malignant melanoma versus the non-metastatic one (12.8 and 5.9, respectively) (21).…”
Section: Lymphatic Microvessel Density (Lmvd)mentioning
confidence: 97%